Belief is not always what you believe it is: Between belief and knowledge - Wiktor Stoczkowski (Anuac, 2015)
We are paradoxically used to calling beliefs ideas we do not believe in, whereas we persist in considering as knowledge ideas we firmly believe in. This subjective distinction between beliefs and knowledge entails two drawbacks: first, it deprives both notions of any heuristic value; secondly, it conceals the fact that our knowledge is partly composed of beliefs. The author proposes to redefine the notion, in order to distinguish two types of beliefs, each of them including simultaneously religious and scientific representations. This definition offers a new outlook on ordinary knowledge: often considered as based on science, reason or common sense, ordinary knowledge constitutes an important part of our modern Western beliefs.